2014
DOI: 10.1136/bjsports-2014-093494.163
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Motion and Muscular Strength Affect Knee Valgus Moment During Single-Leg Landing After Overhead Stroke in Badminton

Abstract: Background Anterior cruciate ligament (ACL) injury in knees opposite to the racket-hand side frequent occurs during single-leg landing after overhead stroke in badminton. Although large lateral inclination of trunk during single-leg landing seems to generate knee valgus moment which causes ACL injury, it has not been examined. Objective To evaluate if there was a correlation between trunk kinematics and knee valgus moment during single-leg landing after overhead stroke, in addition, to evaluate an association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In this regard, trunk rotation and core muscles endurance are integral parts of the improvement power and transfer the energy up to the kinetic chain from lower body to upper body extremity transferred [14], this mechanism confirmed by previous studies which reported significant improvements in trunk strength after core stability training [6,9,12].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In this regard, trunk rotation and core muscles endurance are integral parts of the improvement power and transfer the energy up to the kinetic chain from lower body to upper body extremity transferred [14], this mechanism confirmed by previous studies which reported significant improvements in trunk strength after core stability training [6,9,12].…”
Section: Discussionsupporting
confidence: 76%
“…Previously, core stability exercises were widely used for reducing the injuries of the low back and lower extremities [9,11,12]. Recently, core stability training has been purported to improve player performance [7,[13][14][15], but the previous studies have not supported these claims in badminton sport.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In badminton, the non-contact technique when player landing from the jump after smash overhead stroke, sometimes get injured at knee which probably occurs as a result of reduced strength or instability and balance issues. [7] Balance defined as an ability to maintain a base support with minimal movement actions and dynamically to perform a motor task while maintaining a stable position. Badminton is a dynamic equilibrium process which involves loss of balance in the air to restore balance after landing.…”
Section: Introductionmentioning
confidence: 99%